Réponses

2014-01-05T23:00:29+01:00
A. (2x-1)² = (x+3)² alors il faut tout d'abord que tu simplifie chaque membres
(2x-1)² = 4x² + 4x - 1
(x+3)² = x² + 6x + 9
Ensuite tu remet les membres.
4x² + 4x - 1 = x² + 6x + 9
3x² - 2x - 10 = 0


Meilleure réponse !
2014-01-05T23:39:51+01:00
Bonsoir

a. (2x - 1)² = (x + 3)²
(2x - 1)² - (x + 3)² = 0
[(2x - 1) + (x + 3)][(2x - 1) - (x + 3)] = 0
(2x - 1 + x + 3)(2x - 1 - x - 3) = 0
(3x + 2)(x - 4) = 0
3x + 2 = 0   ou   x - 4 = 0
3x = -2   ou  x = 4
x = -2/3   opu   x = 4

S = {-2/3 ; 4}

b. -6(3x + 4) = 0
3x + 4 = 0/6
3x + 4 = 0 
3x = -4
x = -4/3

S = {-4/3}